Customary Law Associated with Five Integrated Aspects in Developing Traditional Coastal and Marine Protections for Improving Social People Life and Natural Products in Aru Islands Region of Maluku Province, Indonesia - Martinus J. Saptenno; Sostones Sisinaru; Edwin Ubwarin; William A Siahaya; Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
In present on going work, we report the frontier interdisciplinary findings about customary law associated with five integrated aspects such as (1). History, (2). Laws, (3). Culture, (4). Science, and (5). Geoscience (or earth and space science) connected directly to the development of traditional coastal and marine protection to improve social people life in Aru region of 804 small islands with its highest average hills of 50 meter, south east part of Maluku province, Indonesia. The 5 integrated aspects were then investigated to be associated with a system of 6 customary actions as follows: (1). Features, (2). Characters, (3). Connectivity, (4). Sustainable development, (5). Similarity, and (6). Attitudes. Each of these 6 customary actions was very close to an indicator of social people daily lives such as (1) novel idea, (2) services, (3) tradition, (4) social interactions and (5) protections, except for the sustainable development which has been in conjunction with 2 indicators of economy impacts and building strength. The data was collected, identified, and then analyzed by using direct questioner consisted of 50 questions each in 2 different villages of Wokam and Karang Guli. These findings suggest that customary laws practiced traditionally in Aru region are rich or benefits to improve the local people income in order to sustain their traditional coastal and marine life. The research discovery in this simple paper may be applicable to many different fields of study such as in (1) science, (2) engineering and (3) medical practice based on its significant finding of the different between international customary law and the basic principle and essential of customary law.